การนำมาตรการคุมประพฤติมาใช้ประกอบโทษในคดีอาญา - กัลยกร กิจมานะวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Probation consists of the (1) presentence investigation, the process of searching for information in relation to the offender’s behavior, as well as his surrounding environment, so that the court will be able to determine appropriate sanctions for him, and (2) supervision, the measures to ensure that the offender has complied with the court’s determined sanctions or conditions. Supervision includes the assistance measures which will help the offender to adapt himself to society properly. As a result, probation is an important measure to rehabilitate the offender and prevent the repetition of crime. According to the study, the criminal law of the United States of America and the United Kingdom empower the court to order the combination of probation and criminal sanctions sentence in order to help the offender to adapt himself to society and to prevent the repetition of crime. However, under the Criminal Code of Thailand, the probation is only used by the court, as the conditions in the suspension of punishment or the suspension of the determination of punishment and, for the corrections department, as the conditions of the suspension of imprisonment or the reduction of imprisonment period. Therefore, probation is only applied to a specific number of offenders; many offenders have been released without any probation and left struggling to adjust to society. Many of these offenders return to a life of crime. As mentioned above, Thailand should amend the relating law and allow the court to use probation measures as an additional condition to criminal sanctions. This suggestion probation is new and different from the probation as it already exists in the Thai Criminal Code. The application of said probation will help develop the sanction determination system and will be an advantage to both offenders and society. In addition, the court’s sentence will be more flexible and suitable to each offender in order to achieve the purpose of rehabilitate and preventing the repetition of crime